Dealing effectively with the media - Wade, John (Crisp Pub. Menlo ParkUS, 1992)
Provides basic knowledge and skills for dealing comfortably, confidently and efficiently with any sector of the media - TV, radio or print. Describes the goals, priorities and characteristics of media personnel. Provides detailed guidelines for preparing to be interviewed by the media.